The Enalapril Use in Arterial Hypertension Stimulates The Reparative Processes in Fractures of The Proximal Femur - Mykyta Valilshchykov; Volodymyr Babalyan; Тetiana Markina; Marina Kumetchko; Liudmyla Boiko; Sergey Romaev (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: In patients with a fracture of the proximal femur and concomitant arterial hypertension, there is a disturbance of the reparative processes of bone tissue. This research aimed to study the regulation of the reparative processes of fractures of the proximal femur with intramedullary osteosynthesis during the correction of concomitant hypertension, which was examined based on some markers using the rat model.METHODS: The study involved healthy Wistar rats and spontaneously hypertensive rats (SHR). The subjects were then grouped into healthy rats without exposure (1.1) SHR without exposure (2.1), healthy rats with modeled fractures of the proximal femur (1.2), SHR with modeled fractures of the proximal femur (2.2), SHR underwent hypertension correction with enalapril in subgroups without fracture (2.3) and SHR underwent hypertension correction with enalapril in subgroups with fracture (2.4). The levels of interleukin (IL)-6, tumor necrosis factor alpha (TNF-a), IL-10, amino-terminal propeptide procollagen type III (PIIINP), glucose, uric acid, creatinine, urea, cholesterol, and albumin were determined in the blood serum of the animals. Femur preparations were examined after the removal of intramedullary fixation. RESULTS: Serum IL-6 level of animal in group 2.4 (2.297±0.361 pg/mL) were reduced compared to the corresponding indicators of rats in group 2.3 (4.054±0.491 pg/mL, p<0.05). Serum glucose and urea levels of animal in group 2.4 (3.951±0.156 mmol/L, 6.552±0.426 mmol/L, respectively) were significantly reduced in comparison with the group 2.3 (6.384±0.890 mmol/L, 10.369±0.888 mmol/L, respectively). The histological results indicated a positive effect of the drug enalapril on the healing of fractures of the proximal femur in animals with hypertension.CONCLUSION: Correction of arterial hypertension with enalapril in fractures of the proximal femur improves the reparative processes of bone tissue.KEYWORDS: injury healing, remodeling, concomitant diseases, angiotensin-converting enzyme inhibitors, cytokines, growth factor, collagen, biochemical parameters